Respiration pattern variability and related default mode network connectivity are altered in remitted depression - Zamoscik, Vera; Schmidt, Stephanie Nicole Lyn; Gerchen, Martin Fungisai; Samsouris, Christos; Timm, Christina; Kuehner, Christine; Kirsch, Peter (Psychological medicine, 2018)
BackgroundStudies with healthy participants and patients with respiratory diseases suggest a relation between respiration and mood. The aim of the present analyses was to investigate whether emotionally challenged remitted depressed participants show higher respiration pattern variability (RPV) and whether this is related to mood, clinical outcome and increased default mode network connectivity.MethodsTo challenge participants, sad mood was induced with keywords of personal negative life events in individuals with remitted depression [recurrent major depressive disorder (rMDD), n = 30] and matched healthy controls (HCs, n = 30) during functional magnetic resonance imaging. Respiration was measured by means of a built-in respiration belt. Additionally, questionnaires, a daily life assessment of mood and a 3 years follow-up were applied. For replication, we analysed RPV in an independent sample of 53 rMDD who underwent the same fMRI paradigm.ResultsDuring sad mood, rMDD compared with HC showed greater RPV, with higher variability in pause duration and respiration frequency and lower expiration to inspiration ratio. Higher RPV was related to lower daily life mood and predicted higher depression scores as well as relapses during a 3-year follow-up period. Furthermore, in rMDD compared with HC higher main respiration frequency exhibited a more positive association with connectivity of the posterior cingulate cortex and the right parahippocampal gyrus.ConclusionsThe results suggest a relation between RPV, mood and depression on the behavioural and neural level. Based on our findings, we propose interventions focusing on respiration to be a promising additional tool in the treatment of depression.
Gesehen am 02.09.2019